Desquamative gingivitis: Clinical and epidemiological findings in patients from Northern Greece - Chatzisymeonidou Soultana; Papadopoulos Petros; Andreadis Dimitrios; Poulopoulos Athanasios (Balkan Stomatological Society, 2023)
Background/Aim: Desquamative gingivitis (DG) is a clinical feature-sign associated with other several mucocutaneous or systemic diseases and disorders. The aim of this research was to present the clinical and epidemiological characteristics (prevalence, age, sex, extend of lesions, coexistence with underlying pathologies) of a cohort of 200 patients from Northern Greece that exhibited clinical appearance of DG. Material and Methods: 200 patients with DG were referred to the Department of Oral Medicine/Pathology, School of Dentistry, Aristotle University of Thessaloniki during the years 2004-2014. The patients were examined clinically, and a biopsy was performed to settle the diagnosis of any possible underlying disease. The epidemiologic parameters being studied were the gender and age, and the investigated clinical characteristics contained the localization of the lesions and the prevalence in relation to coexisting pathologies, habits etc. Statistics were performed by SPSS 22.00 by chi-square test (p= 0,05) and STATA14 program. Results: Clinically, most DGs cases (81%) were accompanied by erosions-vesicles mainly in buccal mucosa (68%), tongue (29, 5%) and lips (27%). The most common underlying disorders were immune-related mucocutaneous diseases including OLP (55,5%) and MMP (29,5%), followed by erythema multiforme (7%), and pemphigus vulgaris (6%). Overall, most patients (76%) had a localized form of DG at the gingiva of anterior teeth. This finding was more prominent in OLP. Interestingly, the diffuse DG form was mostly found in males. Conclusions: DG constitutes an early or the only clinical sign, mostly indicative for immune-related mucocutaneous disorder. Indeed, a properly taken biopsy can validate an earlier diagnosis and treatment. This would be crucial in order to avoid patient's discomfort and underlying diseases' complications.